Biotic inactivation of the Pseudomonas aeruginosa quinolone signal molecule - Soh, Eliza Ye-Chen; Chhabra, Siri Ram; Halliday, Nigel; Heeb, Stephan; Müller, Christine; Birmes, Franziska S.; Fetzner, Susanne; Cámara, Miguel; Chan, Kok Gan; Williams, Paul (Wiley, 2015)
In Pseudomonas aeruginosa, quorum sensing (QS) regulates the production of secondary metabolites, many of which are antimicrobials that impact on polymicrobial community composition. Consequently, quenching QS modulates the environmental impact of P. aeruginosa. To identify bacteria capable of inactivating the QS signal molecule 2-heptyl-3- hydroxy-4(1H)-quinolone (PQS), a minimal medium containing PQS as the sole carbon source was used to enrich a Malaysian rainforest soil sample. This yielded an Achromobacter xylosoxidans strain (Q19) that inactivated PQS, yielding a new fluorescent compound (I-PQS) confirmed as PQS-derived using deuterated PQS. The I-PQS structure was elucidated using mass spectrometry and nuclear magnetic resonance spectroscopy as 2-heptyl-2-hydroxy-1,2-dihydroquinoline- 3,4-dione (HHQD). Achromobacter xylosoxidans Q19 oxidized PQS congeners with alkyl chains ranging from C1 to C5 and also N-methyl PQS, yielding the corresponding 2-hydroxy-1,2-dihydroquinoline-3,4- diones, but was unable to inactivate thePQSprecursor HHQ. This indicates that the hydroxyl group at position 3 in PQS is essential and that A. xylosoxidans inactivates PQS via a pathway involving the incorporation of oxygen at C2 of the heterocyclic ring. The conversion of PQS to HHQD also occurred on incubation with 12/17 A. xylosoxidans strains recovered from cystic fibrosis patients, with P. aeruginosa and with Arthrobacter, suggesting that formation of hydroxylated PQS may be a common mechanism of inactivation.